Face-to-face and online teaching experience on experimental animals and alternative methods with nursing students: a research study - Juan F. Garcia Sierra; M. Nélida Fernandez Martinez; Cristina Lopez Cadenas; Raquel Diez Laiz; José M. Rodriguez Lago; Ana M. Sahagun Prieto (BMC, 2023)
Abstract Background Animal models are increasingly used in Nursing science to study care approaches. Despite the scientific relevance and the ethical debate surrounding the use of experimental animals, there is a scarcity of scholarly literature exploring this topic in Nursing Schools. Aim To evaluate perceptions and attitudes of nursing students enrolled in a Pharmacology course on the use of experimental animals and implementation of alternative methods, by comparing the experience for two academic years. An interdisciplinary collaboration has also been developed. Methods A descriptive cross-sectional, quantitative study was developed. Undergraduate nursing students were enrolled in the Pharmacology subject at the University of Leon (Spain). The study was carried out in the Pharmacology facilities. Students followed a two-session practical class regarding experimental animals and alternative methods in the Pharmacology course (Degree in Nursing) in two different academic years (2019-20/2020-21). At the end of the activity, they answered a questionnaire to assess their opinions on the use of experimental animals and alternative methods in Pharmacology and the 3Rs principle. Results A comparison of the students' perception with and without direct participation in the evaluation of promazine effects in mice was made. A total of 190 students participated in the teaching experience, providing high scores in all items (4-5 out of 5 points) regarding the teaching experience. Students became also aware of the advantages and disadvantages on the use of experimental animals, as well as the ethical considerations to bear in mind for their use and the need for alternative methods. Conclusions In the students' opinion, the total replacement of animals by alternative techniques was very difficult, and they preferred to do the practice face-to-face. The alternative method designed was useful for the students to accept the employment of experimental animals in biomedical research and education, and know the legislation applied in the protection of animals.